Deportations from Macedonia and their Place in Bulgarian-Macedonian Relationships - Stefan Detchev (Identities, 2023)
The proposed article reveals how the very deportation of Jews from Macedonia in March 1943 is intertwined and strongly depends on the ideas and memory in the two neighboring countries - the Republic of Bulgaria and the Republic of North Macedonia - for the period of 1941-1944, the Holocaust itself, the subsequent time of communist rule, and the transition period after late 1980s and the beginning of 1990s. It shows how a peculiar beginning of the entry of the problem of the deportation of the Jews into the diplomatic quarrel along the Sofia-Skopje axis appeared in 1998. The following first decade of the new 21st century was distinguished by the strong and tangible presence of various Jewish worlds and narratives about the Jews of Macedonia and the old borders of Bulgaria during the Second World War. As a result the narratives about the deportation of Macedonian Jews and the salvation of Bulgarian ones fight each other. In recent years the international Jewish community, more often indirectly than directly, has played an important role in rounding, smoothing and refining both positions - the Bulgarian and the Macedonian one – with necessary corrections in both narratives.